What factors enable social-ecological transformative potential? The role of learning practices, empowerment, and networking - Aaron J. Tuckey; Zuzana V. Harmáčková; Garry D. Peterson; Albert V. Norström; Michele-Lee Moore; Per Olsson; David P. M. Lam; Amanda Jiménez-Aceituno (Ecology and Society, 2023)
Achieving sustainability in the Anthropocene requires radical changes to how human societies operate. The Seeds of Good Anthropocenes (SOGA) project has identified a diverse set of existing initiatives, called “seeds,” that have the potential to catalyze transformations toward more sustainable pathways. However, the empirical investigation of factors and conditions that enable successful sustainability transformations across multiple cases has been scarce. Building on a review of existing theoretical and empirical research, we developed a theoretical framework for assessing three features identified as important to transformative potential of innovative social-ecological initiatives: (1) learning practices, (2) empowerment, and (3) networking. We applied this framework to a set of African-led and Africa-related initiatives that we selected from the SOGA database that were divided into initiatives with more or less transformative potential. We coded the presence or absence of features relating to the theoretical framework using secondary data, and then compared the initiatives using qualitative comparative analysis (QCA). This analysis revealed that of the three features tested, Networking emerged as the most important feature for transformative potential when compared amongst cases. By developing and testing a framework for the comparison of cases we provide a basis for future comparative work to further identify and test properties of cases that enable transformation.